Charge stability of shallow single nitrogen-vacancy centers in lightly boron-doped diamond. (15th June 2022) - Kageura, Taisuke; Sasama, Yosuke; Shinei, Chikara; Teraji, Tokuyuki; Yamada, Keisuke; Onoda, Shinobu; Takahide, Yamaguchi
Abstract: Nitrogen vacancy (NV) centers in diamond must be in a stable negatively charged state for their application to quantum sensing and quantum information processing. In this study, we investigated the charge-state stability of single NV centers in lightly boron-doped diamond ([B] ≈ 1 × 10 15 cm −3 ). Photoluminescence and optically detected magnetic resonance measurements indicated that single NV centers near the diamond surface are negatively charged despite the presence of boron acceptors. This unique phenomenon can be explained by charge transfer between the NV centers and their local environment under laser excitation. This study provides a new perspective on the charge stability of single NV centers in lightly doped diamond and insights for further development of high-performance diamond quantum devices. Graphical abstract: Image 1